Keupayaan penyelesaian masalah persamaan Surd dalam kalangan pelajar Kolej Matrikulasi Kedah: Kes pemahaman dan kesalahan lazim Matematik - Che Yom, Zakaria (2014)
Students' weak understanding of Surd concepts had resulted in their tendency to make errors when solving Surd equation problems. Having an appropriate understanding of Surd is crucial because Surd concepts function as prerequisite knowledge that students need in order to acquire other topics in mathematics. Having a fragile understanding of Surd concepts could result in the students‟ inability to sustain their mathematics performance at higher educational levels. This study was carried out to explore the Kedah Matriculation College students‟ understanding of Surd equations and to identify their common errors when solving such equations problems. The determination of students‟ understanding was based on Skemp‟s (1976) notion of instrumental and relational understanding. The current study also set out to examine the students‟ practice of checking of final answers when solving the problems based on Polya Problem Solving Model (1945) and their ability to perform the process of squaring. More specifically, it analyzed students‟ problem solving of errors according to the five levels of Newman Error Analysis. Fifty-one One-Year Programme (PST) students enrolled in three modules participated in the study. The Surd Equations Test was used to explore the solutions provided by the students. A clinical interview protocol was designed by the researcher. The results indicated that quite a large number of students possessed instrumental understanding compared to those who possessed the requisite relational understanding. It was found that students made errors in processing skills whereby they were unable to perform the process of squaring. The majority of the students had failed to check their answers for the first and second items and tended to perform the checking only if there were two solutions to the Surd problems. Despite having only an instrumental understanding of the squaring process, the students were still able to solve the Surd equations problems. They were however, limited to the forms that were previously learned. Hence, there is a need for Mathematics educators to emphasize on relational understanding as well as instrumental understanding during the Surd teaching and learning process. This study contributes to the research findings in mathematics education and the formation of policy related to the development of mathematics education curriculum for matriculation students.